PORTLAND CEMENT PRODUCTION AND ITS METHODS - Jovliyev Ziyodulla Anvar Ogli (American Journals, 2023)
A brief summary of research into Portland cement manufacturing methods.
Keywords: portland cement, clinker, mineralogical composition, alite, belite, tricalcium aluminate, aluminoferrite, dry method, dry method.